Changes in Functional Status of Patients who Have Had a Stroke during Rehabilitation - Geriuldas Žiliukas; Danguole Drungilienė; Daiva Sudmantienė; Gintautas Minelga (Lithuanian Sports University, 2020)
The aim was to evaluate changes in functional status of patients who have had a stroke during rehabilitation. The sample consisted of 103 patients who have had a stroke and were treated in the section of rehabilitation; 62% of subjects were female, and 38% - male. Subjects ranged in age from 51 to 78 years, and mean age was 68 years. The methods of scientific research: problems in everyday activities were assessed using Barthel index test, cognitive disorders were assessed using the short mental status examination test. We carried out a retrospective analysis of clinical cases of rehabilitated patients, adjusted for age, gender, place of residence, and diagnosis of the disease. Investigations were carried out twice: upon arrival at upon leaving the section of rehabilitation. Because of rehabilitation, the functional status of patients who have had a stroke improved in the total group from 53.6 to 77.3 scores (p < 0.001). Complications reported during in-patient rehabilitation aggravated and worsened the functional status both at the beginning of rehabilitation (42.4 scores) and later (56.9 scores), while the overall functional status improved during the course of rehabilitation. Integrated rehabilitation had an effect for recovery of cognitive functions: using rehabilitation measures a cognitive function improved in 4.8 points at the end of in-patient rehabilitation (p < 0.001). The best improvement was in subject's concentration, memory, and orientation in time and place. Keywords: stroke, functional status, rehabilitation.